The runaway dinner - Ahlberg, Allan; Ingman, Bruce, 1963- (Cambridge, Mass. : Candlewick Press, 2006)
A young boy named Banjo Cannon always eats a sausage for dinner, until the night that his sausage--and the rest of his meal--runs away.
A Junior Library Guild selection.
Accelerated Reader/Renaissance Learning
Keywords: Sausages -- Juvenile fiction; Dinners and dining -- Juvenile fiction